A study on the wetting behaviour of Al-Si-Zn brazing filler on AA7075 and AR500 surface - Mohd Najib Muhamed; Mohd Zaidi Omar; Shahrum Abdullah; Zainuddin Sajuri; Wan Fathul Hakim Wan Zamri; Zainal Ariffin Selamat (Penerbit Universiti Kebangsaan Malaysia, 2020)
This paper presents the results of an experimental study on wetting and spreading of Al-Si-Zn filler metal on AR500 steel and AA7075 aluminium alloy surface. Wetting and spreading conditions of filler metal onto the surface of the metal were analysed by contact angle and spread ratio with different surface conditions. The contact angle is the measured angle between the tangent to the liquid-vapour interface and the surface of the solid. While, spread ratio measured according to the change in diameter of spread shape geometry of filler metal. The use of the low melting temperature of filler metal is increasingly popular since they are able to reduce the effect of heat on metals. However, the low spreading and de-wetting condition have limited the application of filler metal due to the adverse effect of these conditions on the joint ability. However, overall, this study with different surface conditions of these metals is to identify the wetting and spreading behaviour of filler metal. In this work, Al-Si-Zn filler metal heated by torch brazing was applied to AR500 steel and AA7075 aluminium alloy surface with the different type of surface conditions. Experimental results showed that the higher spreading area of filler metal occurred on a smooth surface compared to the rough surface of metals.